2007
DOI: 10.1097/01.dbp.0000257517.52459.7a
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Mothers of Prematurely Born Infants

Abstract: Findings have implications for the support of mothers during hospitalization and in the early years of parenting a preterm infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
240
4
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(289 citation statements)
references
References 49 publications
35
240
4
10
Order By: Relevance
“…A life change may be the birth of a preterm infant or transition to the role of motherhood, whereas chronic stress may relate to demographic variables, such as financial burden, relationship strain, or social discrimination. Researchers have shown that mothers with a newborn in the NICU describe this as an extremely stressful experience [15][16][17][18] , and there is a positive linear association between high stress perception and severe depressive symptoms and poor sleep quality in mothers with preterm infants [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…A life change may be the birth of a preterm infant or transition to the role of motherhood, whereas chronic stress may relate to demographic variables, such as financial burden, relationship strain, or social discrimination. Researchers have shown that mothers with a newborn in the NICU describe this as an extremely stressful experience [15][16][17][18] , and there is a positive linear association between high stress perception and severe depressive symptoms and poor sleep quality in mothers with preterm infants [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Parents experience higher rates of depression, anxiety and symptoms of PTSD. 9,10,[12][13][14][15]17,21,23,28,29 However, there is evidence of personal growth in the face of adversity as these symptoms may improve with time. Tedeschi and Calhoun 33 , in creating a conceptual framework for the study of post-traumatic growth, state that a life crisis that challenges a person's world view is a necessary first step.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a series of studies from the University of North Carolina, investigators surveyed various cohorts of mothers of premature infants requiring mechanical ventilation, premature infants classified as VLBW, medically fragile infants (defined as requiring hospitalization for a life-threatening illness) and infants seropositive for HIV. [17][18][19][20] Nearly one-fifth of the mothers of premature infants and those of HIV-positive infants were at serious risk for depression, even approaching 2 years after delivery. 17,18 Among mothers of premature infants, the greatest risk factor for depression was rehospitalization of the infant, rather than the initial NICU course, suggesting that the disruptions in daily life caused by readmission to the hospital were a major source of stress.…”
Section: Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations